MoS2‐on‐MXene Heterostructures as Highly Reversible Anode Materials for Lithium‐Ion Batteries - Chen, Chi; Xie, Xiuqiang; Anasori, Babak; Sarycheva, Asya; Makaryan, Taron; Zhao, Mengqiang; Urbankowski, Patrick; Miao, Ling; Jiang, Jianjun; Gogotsi, Yury (Angewandte Chemie (International ed.), 2018)
Two‐dimensional (2D) heterostructured materials, combining the collective advantages of individual building blocks and synergistic properties, have spurred great interest as a new paradigm in materials science. The family of 2D transition‐metal carbides and nitrides, MXenes, has emerged as an attractive platform to construct functional materials with enhanced performance for diverse applications. Here, we synthesized 2D MoS2‐on‐MXene heterostructures through in situ sulfidation of Mo2TiC2Tx MXene. The computational results show that MoS2‐on‐MXene heterostructures have metallic properties. Moreover, the presence of MXene leads to enhanced Li and Li2S adsorption during the intercalation and conversion reactions. These characteristics render the as‐prepared MoS2‐on‐MXene heterostructures stable Li‐ion storage performance. This work paves the way to use MXene to construct 2D heterostructures for energy storage applications. MoS2‐on‐MXene heterostructures were obtained by an in situ sulfidation of Mo2TiC2Tx MXene, which deliver improved Coulombic efficiency and cycling performance for the Li‐ion battery. A computational study shows that the strong Li and Li2S adsorption on 2D heterostructures leads to a stable Li‐ion storage performance.